Loneliness and delusion-like experiences among women: Mediating role of procrastination and boredom proneness - Karolina Szalińska (PLoS ONE, 2025)
Delusions, a core psychopathological symptom, occur both in mental disorders and as delusion-like experiences in the general population. This study aimed to examine the relationship between loneliness and delusion-like experiences, considering the mediating roles of procrastination and boredom proneness. The sample consisted of 291 women aged 18–65 years (M = 30.05; SD = 10.298). The analyses revealed that procrastination (Indirect = 0.05; 95%CI [0.01; 0.10] significantly mediated the relationship between loneliness and delusion-like experiences, while boredom proneness showed no significant mediating effect (Indirect = 0.02; 95%CI [−0.01; 0.04]). These findings suggest that procrastination may be a key mechanism underlying the association between loneliness and delusions, with potential implications for therapeutic interventions. The results obtained may serve as a foundation for implementing effective interventions to reduce belief in delusions, stress associated with experiencing delusions, and preoccupation with delusional thoughts. Moreover, understanding the functioning of individuals with delusion-like experiences may support the adaptation of specific therapeutic and support techniques.